Perlindungan Hukum Terhadap Dokter Bedah Yang Melakukan Tindakan Operasi Di Rumah Sakit Charitas Group Palembang - Fauzan, Febrero Andro Dwi; Kasra, Helwan; Salia, Erli (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
This study examines the legal protection of surgeons at Charitas Group Hospital Palembang using a normative juridical and empirical approach. The findings indicate that legal protection is provided through both preventive and repressive measures, which have generally been effective, as reflected in the limited number of medical cases brought to court. Nevertheless, patient complaints still occur but are usually resolved constructively through internal mediation or with the involvement of third parties. Legal protection is granted as long as surgeons fulfill their professional obligations in accordance with the applicable legal framework. Factors influencing such protection include compliance with standard operating procedures (SOP), adherence to clinical pathways, the presence of informed consent, and the observance of medical ethics in healthcare services.